2022
DOI: 10.3389/fpsyg.2022.846594
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Intention to Use Sports Bracelets Among Chinese University Students: An Extension of Technology Acceptance Model With Sports Motivation

Abstract: The use of mobile technology, such as sports bracelets, is gaining popularity as it modifies the ways and processes of learning and teaching in college physical education (PE). However, little empirical evidence can be seen in literature to demonstrate crucial factors that influence university students’ acceptance of sports bracelets. Guided by the technology acceptance model (TAM), this study hence aimed at explaining university students’ intention to use sports bracelets. In total, 445 university students in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…According to Davis (1989), user acceptance plays important role for successful technology implementation. Based on this thought, the technology acceptance model (TAM) originated from the theory of reasoned action and the theory of planned behavior (Wang et al, 2022a) were developed by Davis (1989) to individuals' acceptance or rejection of a technology. The model postulated that system design features has a positive effect on perceived ease of use (PEOU) and perceived usefulness (PU).…”
Section: Theoretical Background and Research Hypothesis 1technology A...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Davis (1989), user acceptance plays important role for successful technology implementation. Based on this thought, the technology acceptance model (TAM) originated from the theory of reasoned action and the theory of planned behavior (Wang et al, 2022a) were developed by Davis (1989) to individuals' acceptance or rejection of a technology. The model postulated that system design features has a positive effect on perceived ease of use (PEOU) and perceived usefulness (PU).…”
Section: Theoretical Background and Research Hypothesis 1technology A...mentioning
confidence: 99%
“…ATT is the degree to which people have a positive or negative evaluations when they act a certain behavior (Ajzen, 1991). In this regard, when ATT is incorporated into educational technology system, recent studies indicated that ATT has significantly affect intentions to use technology in education (Wang et al, 2022a). One of the very rare studies on Web 2.0 technologies was conducted by Sadaf et al (2016).…”
Section: Attitude (Att)mentioning
confidence: 99%